Marine-derived natural polymer-based bioprinting ink for biocompatible, durable, and controllable 3D constructs. (1st April 2019) - Park, Tae Yoon; Yang, Yun Jung; Ha, Dong-Heon; Cho, Dong-Woo; Cha, Hyung Joon
Abstract: 3D bioprinting (3DBP) is a rapid solid-form fabrication method with a high degree of automation and reproducibility for constructing structural bioscaffolds. However, the development of the 3DBP field has been slowed due to difficulty in acquiring suitable ink materials especially with natural polymers that satisfy all requirements, such as printability, mechanical integrity, and biocompatibility. In this study, a new 3DBP ink of bioengineered sea anemone-derived silk-like protein (aneroin) was used based on its durable mechanical properties and biodegradability in previous studies. The hyaluronic acid and mussel adhesive protein (MAP) were applied for improved printability and cell adhesiveness, respectively. The aneroin-based 3DBP ink (named aneroin ink) was solidified in a few second by dityrosine photo-crosslinking, and its fast reaction was suitable for noncollapsed spaces in printed 3D constructs. Actual-sized human ear, vascular graft, and rectangular multi-layered lattice were bioprinted with high controllability and durable structural integrity. Thus, the developed aneroin ink showed good printability, structural integrity, and biocompatibility for successful application to the construction of various 3D shaped bioscaffolds in tissue and biomedical engineering fields.